PERAN KEPEMIMPINAN KEPALA DAERAH DALAM MEWUJUDKAN SISTEM KETAHANAN NASIONAL - Dadang Garnida; Sjafri Mangkuprawira; Aji Hermawan; Bomer Pasaribu (School of Business, Bogor Agricultural University (SB-IPB), 2011)
Leadership is a phenomenon of society, nation, and state which influence and characterize the life of society, nation, and state. Leadership is also one of all functions which can push both the realization of national ideas and national objectives, and national security and defense system. This research seeks for a strategic leadership model which can be implemented in all provinces in Indonesia, and which will influence all of provincial leaders, especially governors, in order to improve the strength of the National Security System (NSS). The collected quantitative and qualitative data were selected and analized descriptively and analitically by the use of descriptive analysis and multivariate regression, to meet the objective of this research. The result of this study shows that the leadership of a governor has a significant and positive influence upon national security and defense system and, therefore, it maybe concluded that a strong leadership of a governor will provide his local area with positive effect, namely, there will be an establishment of a strong and realiable system of national security and defense. Keywords: Leadership, Province, Governor, National Security and Defense System, Multivariate Regression